Islamic Education Based on Local Wisdom in Diniyah Nurul Hidayah Madrasah - Riasah, Eris Siti (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2023)
Madrasah Diniyah Nurul Hidayah is one of the many Madrasah Diniyah in Sukabumi district, located in Jayabakti village, Cidahu sub-district. As one of the private Diniyah Madrasahs in terms of quantity, this Diniyah Madrasah has approximately 350 students consisting of male and female students. This Diniyah Madrasah was established in 1996 in the implementation of comprehensive learning, especially in the development of cognitive and vocational aspects of students which are carried out integrally, optimising effective aspects by strengthening the emotional and spiritual aspects of students. This service aims to assist the implementation of local wisdom-based Islamic education through the implementation of curriculum development and models at Madrasah Diniyah Nurul hidayah. The results show that the implementation of the curriculum carried out is by adding local content of Pegon Arabic, Fasholatan, Barzanji Diba', Yasin Tahlil Sundanese language and Jurumiyah yellow book. The curriculum structure includes Mulok hadrah art, calligraphy, English, and muhadlarah. These curriculum activities were chosen to preserve the local wisdom of Marhaba or earth alms, circumcision, baby birth and haol traditions. This service has implications for the implementation of local wisdom-based Islamic education in Madrasah Diniyah Nurul Hidayah. It is expected that many Diniyah madrasah institutions preserve local wisdom as the basis for the implementation of Islamic education.